Legal regulation of «Cartel» in European Union - Alekseeva , I. M.; Алексеева, И. М.; Алєксєєва, I. M. (Одеса : Фенікс, 2012)
Understanding of cartel’s issues in a today’s economic development can bring to decision that it is time for modernization of anti cartel legislation that helps to uncover most of cartels through leniency program and broader legal liability except imposing fines.
Alekseeva I. M. Legal regulation of «Cartel» in European Union / I. M. Alekseeva // // Міжнародні читання з міжнародного права пам’яті професора П.Є. Казанського : матер. третьої міжнар. наук. конф. (м. Одеса, 2–3 листопада 2012 р.) / відп. за випуск М.І. Пашковський ; Націон. ун-т «Одеська юридична академія». – Одеса : Фенікс, 2012. – С. 594-597.
Keywords: Legal regulation of «Cartel» in European Union; правовое регулирование «картеля» в Европейском Союзе